Kinetika Reaksi Transesterifikasi Minyak Kedelai Menjadi Biodiesel dengan Katalis CaO - Setiarto Pratigto; Istadi Istadi (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2019)
The use of biodiesel is expected to reduce dependence on fossil fuels. In this study, the kinetic reaction of transesterification of soybean oil with methanol will be assessed using heterogeneous CaO solid base catalyst with parameters of mole ratio of reactants to the conversion of methyl ester used to determine the reaction velocity equation. The reaction speed equation is used in the design of a fluidized CSTR (Continues Tank Reactor) reactor to obtain the reactor volume and catalyst weight. The purpose of this study was to determine the form of the velocity reaction equation for soybean and methanol transesterification reactions using CaO catalyst and determine the weight of the catalyst needed by using the reaction speed equation. The study was carried out by transesterification of soybean oil and methanol with CaO catalyst with the independent variable mole ratio of reactants while the fixed variable reaction temperature was 60°C, catalyst weight was 3% (% b/v), reaction time was 180 minutes. The results showed that methanol adsorbed on the surface of the catalyst and triglycerides not adsorbed on the surface of the catalyst showed that the mechanism of the catalytic reaction that occurred was the Eley-Rideal mechanism where one of the reactants was adsorbed on the surface of the catalyst. The form of the speed equation for the transesterification reaction of soybean oil and methanol using a CaO catalyst is . The reaction speed equation is used in the design of the reactor, so that the relationship between the weight of the catalyst needed to convert triglycerides to biodiesel and the predicted calculation of the volume of the reactor used can be done.